Low Vision Management in Chronic Glaucoma: Poster Presentation - Case Report - Resident - Muhammad Fahmi; Ani Ismail; Eva Kumalasari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Glaucoma is a group of progressive optic neuropathy corresponding to peripheral vision loss, causing severe visual impairment to blindness. Low vision is a person who has the best visual acuity in the best eye of 6/18 to light perception or with a visual field of <10 degrees from the fixation point, after medical, surgical, and/or optical intervention. Low vision will affect every aspect of patient’s life, hence precise management of low vision is important. Case Illustration : RY, a woman, 64 years old, works as a housewife. Complained of blurred vision slowly since 3 years ago, especially when reading. The patient then went for treatment to get glasses and was said to have glaucoma. Glaucoma surgery was performed on both patient's eyes and cataract surgery on the right eye. Now the patient’s visual acuity is 6/21 with peripheral vision loss on the right eye and NLP on the left eye. Discussion : The patient was diagnosed with Low Vision et causa Glaucoma. Treatment includes pharmacological treatment, optical and non-optical treatment to carry out daily activities so that the patient remains independent. Education must be explained to patients that there is no therapy to eliminate visual field disturbances but that the use of the remaining visual fields can be maximized. Conclusion : The goal of low vision management in this patient is to maximize central vision and provide visual aids to maximize the patient’s quality of life.